Ethylated Amine Role in the Inhibition of Top of Line Corrosion in Marginally Sour Environments (University of Thi-Qar Journal for Engineering Sciences, 2022)
Carbon steel pipelines used in oil and gas transportation suffer from top of line corrosion (TLC). This persistent issue endangers the safety of the pipeline network. Corrosion at 10-2 o’clock position could occur as a result of the condensation process of water vapor containing CO2 and H2S acidic gases. Due to the difficulty of reaching inhibitors to the top of the pipeline, this type of corrosion represents a big challenge to the oil and gas industry. The injection of corrosion inhibitors is a typical method for corrosion mitigation. The conventional corrosion inhibitors employ in the petroleum industry are non-volatile liquids, and they hardly reach to the top of the pipeline where the condensed water which contains corrosive species, for instance, CO2 and H2S is accumulated. Rendering this mitigation technique unable to prevent the TLC, therefore, TLC is a major challenge in the oil and gas industry. This study details the work carried out to develop an inhibitor performance and presents a novel volatile corrosion inhibitor that prevents the TLC in marginally sour environments. An innovative glass cell setup was designed and applied in the study, to simulate the TLC process in conditions similar to field experience and to improve the experimental data quality. Weight loss measurement technique was conducted to find the TLC rates in the presence and the absence of the volatile corrosion inhibitor. The gas-phase concentrations of H2S started from 0.015 of up to 0.15 mbar. . Upon injection of the inhibitor, the results showed that the developed inhibitor could effectively mitigate and reduce the corrosion rate at the top of the pipe which suggests its potential application in the oil and gas industry.